2008
DOI: 10.1016/j.bbmt.2008.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Outcomes of HLA-Matched Related, Unrelated, or HLA-Haploidentical Related Hematopoietic Cell Transplantation following Nonmyeloablative Conditioning for Relapsed or Refractory Hodgkin Lymphoma

Abstract: We compared the outcome of nonmyeloablative allogeneic hematopoietic cell transplantation (HCT) for patients with relapsed or refractory Hodgkin lymphoma (HL) based on donor cell source. Ninety patients with HL were treated with nonmyeloablative conditioning followed by HCT from HLA-matched related, n = 38, unrelated, n = 24, or HLA-haploidentical related, n = 28 donors. Patients were heavily pretreated with a median of 5 regimens and most patients had failed autologous HCT (92%) and local radiation therapy (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
197
6
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(230 citation statements)
references
References 48 publications
19
197
6
8
Order By: Relevance
“…Furthermore, PT-CY does not affect engraftment due to the enzymatic resistance of hemopoietic stem cells to CY, possibly, because most stem cells are not dividing. 17 In a retrospective study, the Baltimore group showed that the outcome of HL patients receiving a haploidentical transplant with PT-CY is comparable, if not superior, to the outcome of patients grafted from HLA identical sibling or unrelated donors. 18 The aim of this retrospective study was to confirm the reproducibility of the procedure in terms of toxicity and efficacy in a cohort of HL patients treated in two institutions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, PT-CY does not affect engraftment due to the enzymatic resistance of hemopoietic stem cells to CY, possibly, because most stem cells are not dividing. 17 In a retrospective study, the Baltimore group showed that the outcome of HL patients receiving a haploidentical transplant with PT-CY is comparable, if not superior, to the outcome of patients grafted from HLA identical sibling or unrelated donors. 18 The aim of this retrospective study was to confirm the reproducibility of the procedure in terms of toxicity and efficacy in a cohort of HL patients treated in two institutions.…”
Section: Introductionmentioning
confidence: 99%
“…60,61,67 Three recent publications focused on the use of alternative donors and contributed to outline the role of HLA matching on outcome. [68][69][70] These data underline the feasibility of RIC allo-HCT and suggest searching for a suitable donor, either a MRD or an alternative one, as soon as relapse after an auto-HCT occurs.…”
Section: Monoclonal Antibodiesmentioning
confidence: 85%
“…22 This benefit has been difficult to prove clinically, as there are no prospective randomized trials evaluating the antitumor efficacy of haploidentical HCT compared with matched related or unrelated donor stem cell transplants. Surprisingly, a higher relapse probability was observed in a retrospective analysis of the outcomes of transplants from T cell-depleted related and unrelated donors, one Agmismatched donors and haploidentical related donors by Drobyski et al 23 On the other hand, Burroughs et al 24 showed that relapse probabilities were lower following nonmyeloablative low-dose TBI-based haploidentical non-T cell-depleted SCT than HLA-matched related or unrelated donor HCT. Given the higher risk of GVHD following haploidentical HCT and the frequent need for aggressive immunosuppressive therapy to treat the GVHD, it is possible that much of the antitumor effect is abrogated by this potent immunosuppressive therapy.…”
Section: Haploidentical Hematopoietic Cell Transplantationmentioning
confidence: 99%